MARKETING STRATEGY ANALYSIS IN INCREASING THE NUMBER OF CONSUMERS AND TURNOVER IN THE COFFEE SHOP BUSINESS IN MEDAN CITY - Hafiz Ahmad; Zulkarnain Lubis; Yusniar Lubis (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze how marketing strategies can increase the number of consumers and turnover in Coffee Shop businesses in Medan City. The methods used in this study are qualitative and quantitative research. The data collection studied in this study amounted to 10 coffee shops taken from various locations. The data analysis technique used in this study is Spearman rank correlation analysis. The results of this study indicate that the product has a significant correlation with turnover and an increase in the number of coffee shop consumers in Medan City. Price has an opposite effect to the Number of Consumers, while on turnover it shows that price has an effect in the same direction as Turnover. The results of the study also show a significant relationship between price and Coffee Shop Turnover in Medan City. Location has a weak but significant effect on the Number of Consumers and turnover Coffee shop turnover in Medan City. Likewise, Promotion has a unidirectional and significant relationship between promotion and the Number of Coffee Shop Consumers. While on turnover, promotion has an opposite effect to Turnover and has a significant relationship between promotion and Coffee Shop Turnover in Medan City. The process has an effect in the same direction as the Number of Consumers, while on turnover it shows an insignificant relationship between the process and Coffee Shop Turnover in Medan City. There is an influence between HR and the Number of Coffee Shop Consumers in Medan City, while turnover shows an insignificant relationship between HR and Coffee Shop Turnover in Medan City. The results of this study indicate a significant relationship between Physical Evidence and the Number of Consumers and Coffee Shop Turnover in Medan City.